Aluminum nitride-based laminated resistive random access memory and preparation method thereof

By using a stacked aluminum nitride-based memory in RRAM devices, using AlN layers with different nitrogen contents to form hourglass-shaped conductive filaments, the problems of unstable device performance and high cost are solved, and higher consistency and Lower power consumption memory devices.

CN119212546APending Publication Date: 2024-12-27XIDIAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411272026.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The resistance-change conversion parameters in existing RRAM devices are difficult to control, resulting in unstable device performance, and the single-layer aluminum nitride devices have random conductive channel formation and fracture, which increases production costs and difficult to scale.

Method used

A stacked resistive memory structure with an aluminum nitride-based layer includes a first AlN layer, a second AlN layer and a third AlN layer stacked from bottom to top, and the nitrogen content of the second AlN layer is higher than that of the first AlN layer and The third AlN layer forms an hourglass-shaped conductive filament by regulating the flow ratio of nitrogen and argon to stabilize the resistance and change parameters of the device.

Benefits of technology

The device has achieved higher consistency of resistance-change parameters, improved overall performance stability, improved durability, reduced switching current, and achieved a lower power consumption resistance-change memory.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119212546A_ABST
    Figure CN119212546A_ABST
Patent Text Reader

Abstract

The invention discloses an aluminum nitride-based laminated resistive random access memory and a preparation method thereof, and relates to the technical field of semiconductors, and the aluminum nitride-based laminated resistive random access memory comprises a substrate layer, an adhesion layer, a bottom electrode layer, an AlN resistive random access layer, a top electrode layer and a protection layer which are sequentially laminated from bottom to top, the AlN resistive layer comprises a first AlN layer, a second AlN layer and a third AlN layer which are sequentially stacked from bottom to top, and the nitrogen content of the second AlN layer is higher than that of the first AlN layer and that of the third AlN layer. According to the invention, the aluminum nitride resistance change layer is formed by the three AlN layers with different nitrogen element proportions, so that the accumulation of nitrogen vacancies in the nitrogen-rich second AlN layer can be limited, the conductive filaments are stably broken in the middle nitrogen-rich aluminum nitride layer in the resetting process of the device, the resistance change parameter consistency of the device is higher, and the overall performance of the device is higher in stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of semiconductors, and in particular relates to an aluminum nitride-based laminated resistive random access memory and a preparation method thereof. Background Art

[0002] In recent years, with the continuous reduction in the size of semiconductor devices, traditional volatile memory faces technical bottlenecks in many aspects, such as difficulty in further scaling of processes, lack of reliability guarantee and excessive power consumption, making it difficult to meet the rapidly growing storage needs. New non-volatile memories with high performance and low energy consumption are expected to become the next generation of mainstream semiconductor memories, among which resistive random access memory (RRAM) as an emerging non-volatile memory has become a strong candidate.

[0003] The structure of RRAM devices is similar to the traditional sandwich structure (MIM), which consists of an upper electrode, a working layer, and a lower electrode. Pt, Au, Ti, Cu, Ag, or TiN are usually used as electrode materials. Organic matter, transition metal oxides, nitrides, and two-dimensional materials can all be used as working layers. At present, nitride resistive switching materials have been widely studied, such as CuN, SiN, AlN, etc. Among them, AlN as the working layer of RRAM has good resistive switching performance such as extremely fast switching speed and low power consumption.

[0004] However, since the resistive switching parameters in RRAM devices are mainly controlled by the conduction and disconnection of the randomly formed local conductive filaments in the film, and the conductive filaments are limited by the randomness of the internal defect state of the prepared device, the resistive switching parameters (mainly including the on and off voltage values ​​and the on and off resistance values) are relatively diffuse and difficult to control, which is a huge challenge for the effective writing and erasing of device storage information. Secondly, there is only one metal-semiconductor interface in the single-layer aluminum nitride device, and the nitrogen ion concentration and nitrogen vacancies cannot be adjusted, resulting in a random increase in the formation and breakage of the conductive channel and unstable device performance. For this reason, researchers have proposed many methods to improve stability, such as introducing nanocrystals in the working layer, impurity doping, and preparing a conical upper electrode with concentrated electric field. However, these solutions require additional microstructure processing, sacrificing the scalability of miniaturization and increasing production costs. Summary of the invention

[0005] In order to solve the above problems existing in the prior art, the present invention provides an aluminum nitride-based stacked resistive random access memory and a preparation method thereof. The technical problem to be solved by the present invention is achieved by the following technical solutions:

[0006] The present invention provides an aluminum nitride-based stacked resistive random access memory, comprising: a substrate layer, an adhesion layer, a bottom electrode layer, an AlN resistive random access layer, a top electrode layer and a protective layer, wherein:

[0007] The substrate layer, the adhesion layer, the bottom electrode layer and the AlN resistive switching layer are stacked in sequence from bottom to top;

[0008] The AlN resistive layer comprises a first AlN layer, a second AlN layer and a third AlN layer stacked in sequence from bottom to top, wherein the nitrogen content of the second AlN layer is higher than that of the first AlN layer and the third AlN layer;

[0009] The top electrode layer is patterned and arranged on the upper surface of the AlN resistive layer, and the protection layer is arranged on the upper surface of the top electrode layer.

[0010] In one embodiment of the present invention, the substrate layer includes a Si substrate and a SiO2 layer on its upper surface, wherein the Si substrate is a P-type Si substrate with a <1 1 1> crystal plane, and the adhesion layer is located on the upper surface of the SiO2 layer.

[0011] In one embodiment of the present invention, the adhesion layer is a Ti metal layer with a thickness of 5-10 nm, and the bottom electrode layer is a Pt metal layer with a thickness of 50-100 nm.

[0012] In one embodiment of the present invention, the nitrogen content of the first AlN layer is 10% to 15%, and the thickness is 8-10 nm.

[0013] In one embodiment of the present invention, the nitrogen content of the second AlN layer is 40% to 45%, and the thickness is 4-6 nm.

[0014] In one embodiment of the present invention, the nitrogen content of the third AlN layer is 10% to 15%, and the thickness is 8-10 nm.

[0015] In one embodiment of the present invention, the top electrode layer is an Al metal layer with a thickness of 50-100 nm, and the protective layer is an Au metal layer with a thickness of 50-100 nm.

[0016] The present invention provides a method for preparing an aluminum nitride-based stacked resistive random access memory, which is applicable to the aluminum nitride-based stacked resistive random access memory described in any one of the above embodiments. The preparation method comprises:

[0017] Step 1: performing thermal oxidation treatment on the Si substrate to form a SiO2 layer on the upper surface of the Si substrate to obtain a substrate layer;

[0018] Step 2: depositing a Ti metal layer on the upper surface of the SiO2 layer of the substrate layer to form an adhesion layer, and depositing a Pt metal layer on the upper surface of the Ti metal layer to form a bottom electrode layer;

[0019] Step 3: stacking a first AlN layer, a second AlN layer and a third AlN layer in sequence from bottom to top on the upper surface of the bottom electrode layer to form an AlN resistive layer, wherein the nitrogen content of the second AlN layer is higher than that of the first AlN layer and the third AlN layer, and the nitrogen content of the first AlN layer, the second AlN layer and the third AlN layer is regulated by the flow ratio of nitrogen gas to argon gas introduced during the preparation process;

[0020] Step 4: etching the AlN resistive layer to expose a portion of the bottom electrode layer below the AlN resistive layer;

[0021] Step 5: preparing a patterned top electrode layer on the upper surface of the AlN resistive layer, and preparing a protective layer on the upper surface of the top electrode layer.

[0022] In one embodiment of the present invention, step 3 comprises:

[0023] A first AlN layer, a second AlN layer and a third AlN layer are sequentially deposited on the upper surface of the bottom electrode layer from bottom to top by a magnetron sputtering process to form an AlN resistive layer, wherein when depositing the first AlN layer and the third AlN layer, the flow ratio of argon gas to nitrogen is (2.8-3.2):1, and when depositing the second AlN layer, the flow ratio of argon gas to nitrogen is (0.2-0.6):1.

[0024] In one embodiment of the present invention, step 3 comprises:

[0025] A plasma enhanced atomic layer deposition process is used to deposit a first AlN layer, a second AlN layer and a third AlN layer in sequence from bottom to top on the upper surface of the bottom electrode layer to form an AlN resistive layer, wherein when depositing the first AlN layer and the third AlN layer, the flow ratio of argon gas to nitrogen-hydrogen mixed gas is (2-3):1, and when depositing the second AlN layer, the flow ratio of argon gas to nitrogen-hydrogen mixed gas is (0.6-1):1.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] The aluminum nitride-based stacked resistive random access memory of the present invention, the AlN resistive random access layer includes a first AlN layer, a second AlN layer and a third AlN layer of a stacked structure, and the nitrogen content of the second AlN layer is higher than that of the first AlN layer and the third AlN layer. The main body of the functional layer of the stacked structure is a nitrogen-rich second AlN layer, and three AlN layers with different nitrogen element proportions form an aluminum nitride resistive random access layer, which can limit the accumulation of nitrogen vacancies in the nitrogen-rich second AlN layer, so that the conductive filaments are in an hourglass-shaped structure, and are stable in the middle of the nitrogen-rich aluminum nitride layer during the device reset process. The resistive random access parameters of the device, that is, the on-off voltage value and the on-off resistance value are more consistent, the overall performance of the device presents higher stability, and the durability is correspondingly improved. At the same time, due to the presence of the nitrogen-rich aluminum nitride layer, the reduction of trap centers can effectively block the charge, thereby reducing the switching current of the device and realizing a resistive random access memory with lower power consumption.

[0028] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present invention more obvious and easy to understand, the following specifically cites a preferred embodiment and describes it in detail with the accompanying drawings as follows. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is a schematic structural diagram of an aluminum nitride-based stacked resistive random access memory provided by an embodiment of the present invention;

[0030] Figure 2 It is a flow chart of a method for preparing an aluminum nitride-based stacked resistive random access memory provided by an embodiment of the present invention;

[0031] Figure 3 It is a schematic diagram of a preparation process of an aluminum nitride-based stacked resistive random access memory provided by an embodiment of the present invention.

[0032] Icon: 1-substrate layer; 11-Si substrate; 12-SiO2 layer; 2-adhesion layer; 3-bottom electrode layer; 4-AlN resistive layer; 41-first AlN layer; 42-second AlN layer; 43-third AlN layer; 5-top electrode layer; 6-protective layer. DETAILED DESCRIPTION

[0033] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, an aluminum nitride-based stacked resistive random access memory and a preparation method thereof proposed in accordance with the present invention are described in detail below in conjunction with the accompanying drawings and specific implementation methods.

[0034] The above and other technical contents, features and effects of the present invention are clearly presented in the following detailed description of the specific implementation modes in conjunction with the accompanying drawings. Through the description of the specific implementation modes, the technical means and effects adopted by the present invention to achieve the predetermined purpose can be more deeply and specifically understood. However, the attached drawings are only for reference and explanation purposes and are not used to limit the technical solutions of the present invention.

[0035] In a first aspect, an embodiment of the present invention provides an aluminum nitride-based stacked resistive random access memory, see Figure 1 , Figure 1 Schematic diagram of the structure of an aluminum nitride-based stacked resistive random access memory provided by an embodiment of the present invention. Figure 1 As shown, the aluminum nitride-based stacked resistive memory of this embodiment includes: a substrate layer 1, an adhesion layer 2, a bottom electrode layer 3, an AlN resistive layer 4, a top electrode layer 5 and a protective layer 6. Among them, the substrate layer 1, the adhesion layer 2, the bottom electrode layer 3 and the AlN resistive layer 4 are stacked in sequence from bottom to top; the AlN resistive layer 4 includes a first AlN layer 41, a second AlN layer 42 and a third AlN layer 43 stacked in sequence from bottom to top, and the nitrogen content of the second AlN layer 42 is higher than that of the first AlN layer 41 and the third AlN layer 43; the top electrode layer 5 is patterned on the upper surface of the AlN resistive layer 4, and the protective layer 6 is arranged on the upper surface of the top electrode layer 5.

[0036] In the aluminum nitride-based stacked resistive memory of the embodiment of the present invention, the AlN resistive layer includes a first AlN layer, a second AlN layer and a third AlN layer of a stacked structure, and the nitrogen content of the second AlN layer is higher than that of the first AlN layer and the third AlN layer. The main body of the functional layer of the stacked structure is a nitrogen-rich second AlN layer, and three AlN layers with different nitrogen element proportions form an aluminum nitride resistive layer, which can limit the accumulation of nitrogen vacancies in the nitrogen-rich second AlN layer, so that the conductive filaments are in an hourglass-shaped structure, and are stable in the middle of the nitrogen-rich aluminum nitride layer during the device reset process. The resistive parameters of the device, that is, the on-off voltage values ​​and the on-off resistance values ​​are more consistent, the overall performance of the device presents higher stability, and the durability is correspondingly improved. At the same time, due to the presence of the nitrogen-rich aluminum nitride layer, the reduction of trap centers can effectively block the charge, thereby reducing the switching current of the device and realizing a resistive memory with lower power consumption.

[0037] In an optional embodiment, the substrate layer 1 includes a Si substrate 11 and a SiO2 layer 12 on its upper surface. The Si substrate 11 is a P-type Si substrate with a <1 1 1> crystal plane, and the adhesion layer 2 is located on the upper surface of the SiO2 layer 12.

[0038] In an optional embodiment, the adhesion layer 2 is a Ti metal layer with a thickness of 5-10 nm, and the bottom electrode layer 3 is a Pt metal layer with a thickness of 50-100 nm.

[0039] In an optional embodiment, the nitrogen content of the first AlN layer 41 is 10% to 15% and the thickness is 8-10 nm. The nitrogen content of the second AlN layer 42 is 40% to 45% and the thickness is 4-6 nm. The nitrogen content of the third AlN layer 43 is 10% to 15% and the thickness is 8-10 nm.

[0040] In this embodiment, the proportion of nitrogen in the first AlN layer 41 , the second AlN layer 42 and the third AlN layer 43 can be controlled by the flow ratio of nitrogen gas and argon gas introduced during the preparation process.

[0041] In an optional embodiment, the top electrode layer 5 is an Al metal layer with a thickness of 50-100 nm, and the protective layer 6 is an Au metal layer with a thickness of 50-100 nm.

[0042] In this embodiment, the top electrode layer 5 includes a plurality of Al metal cylindrical electrodes arranged in an array, and the axes of the cylindrical electrodes are perpendicular to the bottom electrode layer 3. The protective layer 6 is located on the top of the Al metal cylindrical electrodes.

[0043] The aluminum nitride-based stacked resistive memory of the embodiment of the present invention has an AlN resistive layer with a thickness of about 20 nm. Compared with a structure in which nanocrystals are introduced into a working layer, impurity doping is performed, and a conical upper electrode with concentrated electric field is prepared to improve device stability, the aluminum nitride-based stacked resistive memory of the embodiment of the present invention does not require additional microstructure processing and will not affect the scalability of device miniaturization.

[0044] In a second aspect, an embodiment of the present invention provides a method for preparing an aluminum nitride-based stacked resistive random access memory, which is applicable to the aluminum nitride-based stacked resistive random access memory provided in the first aspect. Figure 2 , Figure 2 FIG. 1 is a flow chart of a method for preparing an aluminum nitride-based stacked resistive random access memory provided by an embodiment of the present invention. Figure 2 As shown, the method for preparing the aluminum nitride-based stacked resistive random access memory of this embodiment includes:

[0045] Step 1: Perform thermal oxidation treatment on the Si substrate to form a SiO2 layer on the upper surface of the Si substrate to obtain a substrate layer.

[0046] Optionally, the thickness of the SiO2 layer is 100 nm. After the SiO2 layer is formed on the upper surface of the Si substrate by thermal oxidation treatment, the surface of the substrate layer can also be ultrasonically cleaned to remove stains, dust and organic impurities on the surface of the substrate layer to ensure good adhesion between the substrate layer and the subsequently prepared adhesion layer.

[0047] Exemplarily, the cleaning process may include three steps: first, ultrasonic cleaning with acetone for 3 minutes, with an ultrasonic intensity of 3. Then, ultrasonic cleaning with anhydrous ethanol for 3 minutes, with an ultrasonic intensity of 3. Finally, rinsing with deionized water for 2 minutes and drying with a nitrogen gun until the surface of the substrate layer is observed to be dry and free of contaminants.

[0048] Step 2: depositing a Ti metal layer on the upper surface of the SiO2 layer of the substrate layer to form an adhesion layer, and depositing a Pt metal layer on the upper surface of the Ti metal layer to form a bottom electrode layer.

[0049] Optionally, a high vacuum evaporation coating device may be used to successively deposit a 5-10 nm Ti metal layer as an adhesion layer and a 50-100 nm Pt metal layer as a bottom electrode layer on the SiO2 layer of the substrate layer.

[0050] For example, during the evaporation process, the chamber temperature is about 25°C and the vacuum degree is less than 5×10 -4 Pa, the deposition rate is about

[0051] It is worth noting that in order to ensure the uniformity of the AlN film of the resistive layer deposited on the bottom electrode layer, after the bottom electrode layer is prepared, XRD (phase analysis of xray diffraction) and AFM (Atomic Force Microscope) equipment can be used to characterize the crystal orientation and roughness of the bottom electrode layer to ensure that the prepared Pt electrode has a <1 1 0> crystal orientation and low roughness.

[0052] Step 3: On the upper surface of the bottom electrode layer, a first AlN layer, a second AlN layer and a third AlN layer are stacked in sequence from bottom to top to form an AlN resistive layer, wherein the nitrogen content of the second AlN layer is higher than that of the first AlN layer and the third AlN layer, and the nitrogen content of the first AlN layer, the second AlN layer and the third AlN layer is regulated by the flow ratio of nitrogen and argon introduced during the preparation process.

[0053] In an optional embodiment, a magnetron sputtering process can be used to deposit a first AlN layer, a second AlN layer and a third AlN layer in sequence from bottom to top on the upper surface of the bottom electrode layer to form an AlN resistive layer, wherein when depositing the first AlN layer and the third AlN layer, the flow ratio of argon and nitrogen is (2.8-3.2):1, and when depositing the second AlN layer, the flow ratio of argon and nitrogen is (0.2-0.6):1.

[0054] Exemplarily, after the bottom electrode layer is prepared, the sample is cleaned and placed in a magnetron sputtering reaction chamber, and a metal Al target with a purity of 99.9995% is used for sputtering. In order to prevent air impurity contamination, the vacuum degree of the sputtering chamber is pumped to less than 1E-6Pa before reactive sputtering to ensure that the impurity gas content in the sputtering chamber is sufficiently low. The working gas is high-purity argon and high-purity nitrogen. Argon is introduced before the film is deposited. A 50W radio frequency source is used to reversely sputter and bombard the sample surface for 5 minutes to remove the oxide layer on the sample surface and nitride the sample surface. The Al target is pre-sputtered, and a DC of 50W is used for sputtering for 5 minutes to remove the oxide layer and impurities on the Al target surface. Then the substrate temperature is set, and the substrate is heated to the target temperature. Finally, an argon-nitrogen mixed gas is introduced in proportion, and the sputtering power and substrate speed are set. The pre-sputtering is performed for 5 minutes so that the target voltage and current reach a stable state to ensure that the deposition rate of the film is relatively constant, and the baffle is opened to start depositing the AlN film.

[0055] It should be noted that in order to ensure the process uniformity of the three-layer aluminum nitride film, the total sputtering gas pressure, target substrate distance, DC sputtering power and substrate temperature are maintained unchanged during the preparation process, and only the ratio of nitrogen and argon in the working gas is changed. In order to prevent the deformation and cracking of the Si wafer caused by the excessively fast heating rate, the heating rate of the substrate is set to 10°C / min. After substrate pre-sputtering and target pre-sputtering, the substrate temperature is raised to 500-600°C.

[0056] First, the first AlN layer, i.e., the nitrogen-deficient aluminum nitride layer, is prepared. The pressure in the chamber can be set to 0.2-0.3Pa, the flow ratio of argon and nitrogen is (2.8-3.2):1, the sputtering power is set to 120-160W, and the sputtering time is 10-12min, so as to prepare the first AlN layer with a thickness of 8-10nm. Then, the second AlN layer, i.e., the nitrogen-rich aluminum nitride layer, is prepared. The substrate temperature and target power are kept unchanged, the pressure in the chamber is still 0.2-0.3Pa, the flow ratio of argon and nitrogen is set to (0.2-0.6):1, and the sputtering time is 5-6min, so as to prepare the second AlN layer with a thickness of 4-6nm. Finally, the third AlN layer with a thickness of 8-10nm, i.e., the nitrogen-deficient aluminum nitride layer, is prepared by sputtering according to the same parameters as the first AlN layer.

[0057] In an optional embodiment, a plasma enhanced atomic layer deposition process (PEALD) can be used to deposit a first AlN layer, a second AlN layer and a third AlN layer in sequence from bottom to top on the upper surface of the bottom electrode layer to form an AlN resistive layer, wherein when depositing the first AlN layer and the third AlN layer, the flow ratio of argon gas and nitrogen-hydrogen mixed gas is (2-3):1, and when depositing the second AlN layer, the flow ratio of argon gas and nitrogen-hydrogen mixed gas is (0.6-1):1.

[0058] Exemplarily, high-purity trimethylaluminum (TMA, Al(CH3)3, 99.999%) is selected as a precursor, high-purity nitrogen-hydrogen mixed gas plasma (10-30sccm, 99.999%) is used as a reactant, and high-purity argon (Ar, 99.999%) is used as a protective gas and a carrier gas (10-15sccm); the sample after the preparation of the bottom electrode layer is placed in a reaction chamber, the sample temperature is 200-300°C; the plasma generation power is 100-150W; the gas pressure of the reaction chamber is 0.15-0.25Torr.

[0059] Each PEALD cycle consists of a precursor injection process, a precursor cleaning process, a reactant injection process, and a reactant cleaning process, and then a corresponding number of cycles are deposited to obtain an AlN film of the desired thickness. The cycle parameters of the PEALD-AlN film are based on the gas path structure of the equipment and the empirical values ​​adopted by existing research.

[0060] First, the first AlN layer, i.e., the nitrogen-deficient aluminum nitride layer, is prepared. The flow ratio of argon and nitrogen-hydrogen mixed gas is set to (2-3):1, and the number of cycles is set to 80-100, so as to prepare a first AlN layer with a thickness of 8-10nm. Then, the second AlN layer, i.e., the nitrogen-rich aluminum nitride layer, is prepared. Keeping other parameters unchanged, the flow ratio of argon and nitrogen-hydrogen mixed gas is set to (0.6-1):1, and the number of cycles is set to 40-60, so as to prepare a second AlN layer with a thickness of 4-6nm. Finally, the third AlN layer with a thickness of 8-10nm, i.e., the nitrogen-deficient aluminum nitride layer, is prepared by cycling 80-100 times according to the same parameters as the first AlN layer.

[0061] Step 4: Etching the AlN resistive layer to expose a portion of the bottom electrode layer below the AlN resistive layer.

[0062] Since no covering is performed during the growth of the AlN resistive layer, a portion of the bottom electrode layer needs to be reserved through an etching process to facilitate subsequent electrical testing.

[0063] In an optional embodiment, the AlN resistive switching layer may be etched using a wet etching process.

[0064] For example, the grown AlN resistive layer can be clamped with tweezers, and one end can be placed in a solution of phosphoric acid: acetic acid: nitric acid: water = 16:1:1:2 for etching for 15-20 seconds. After etching, rinse with deionized water for 120 seconds, and finally blow dry the wafer with N2. After etching, obvious color difference can be observed.

[0065] Step 5: Prepare a patterned top electrode layer on the upper surface of the AlN resistive layer, and prepare a protective layer on the upper surface of the top electrode layer.

[0066] In an optional embodiment, the top electrode layer and the protective layer may be prepared by using a magnetron sputtering process in combination with a circular hard mask template, and the grid size of the hard mask template is a square of 100 μm.

[0067] For example, the hard mask is adhered to the grown AlN resistive layer with a high temperature tape, and then a 50-100 nm Al metal layer as a top electrode layer and a 50-100 nm Au metal layer as a protective layer are deposited in sequence by magnetron sputtering. In this embodiment, the protective layer is used to prevent the top electrode layer from being oxidized and the probe from damaging the electrode during the test process.

[0068] Specifically, the sample with the hard mask was placed in a magnetron sputtering reaction chamber, and a metal Al target with a purity of 99.9995% and a metal Au target with a purity of 99.999% were used for deposition. The equipment was evacuated to 5×10 -7 Pa, first the Al target sputtering power is 450-500W, the chamber pressure is 0.15-0.2Pa, the sputtering gas Ar is introduced, and under the condition of sputtering temperature at room temperature, a top electrode layer with a thickness of 50-100nm is deposited. Then the Au target sputtering power is 150-200W, and a protective layer with a thickness of 50-100nm is deposited under the same conditions. Finally, the hard mask is removed, and then the device sample is cleaned with acetone, ethanol and deionized water and blown dry with nitrogen. When the surface is dry and free of particles, an aluminum nitride-based laminated resistive memory is obtained.

[0069] In an optional embodiment, the top electrode layer and the protective layer may be prepared by using a magnetron sputtering process combined with a photolithography and development technology.

[0070] Exemplarily, a layer of photoresist is thrown on the AlN resistive switching layer after etching, and after exposure and development, a pattern of the top electrode layer is made to deposit the top electrode metal layer. Subsequently, a metal Al layer with a thickness of 50-100nm is deposited on the surface covered with the patterned photoresist by magnetron sputtering as the top electrode layer. Then, a metal Au with a thickness of 50-100nm is deposited on the top electrode layer as a protective layer. Finally, the grown sample is placed in acetone, and ultrasonic vibration is used to remove the photoresist and the metal on the photoresist to obtain an aluminum nitride-based laminated resistive switching memory.

[0071] The method for preparing the aluminum nitride-based stacked resistive random access memory of the embodiment of the present invention is compatible with the current microelectronics process and can be effectively applied to future silicon-based nanoelectronic devices.

[0072] See also Figure 3 , Figure 3is a schematic diagram of a preparation process of an aluminum nitride-based stacked resistive random access memory provided by an embodiment of the present invention. Figure 3 The technical scheme of the present invention is clearly and completely described in detail with specific embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0073] Example 1

[0074] Step 1: Perform thermal oxidation treatment on the P-type Si substrate with the <1 1 1> crystal plane to form a SiO2 layer with a thickness of 100 nm on the upper surface of the Si substrate to obtain a substrate layer. Use acetone, anhydrous ethanol and deionized water to ultrasonically clean the surface of the substrate layer for 3 minutes in sequence and then blow dry with a nitrogen gun.

[0075] Step 2: Using high vacuum evaporation coating equipment, a 5nm Ti metal layer as an adhesion layer and a 50nm Pt metal layer as a bottom electrode layer are deposited on the SiO2 layer of the substrate layer. During the evaporation process, the chamber temperature is about 25°C and the vacuum degree is less than 5×10 -4 Pa, the deposition rate is about

[0076] Step 3: After the bottom electrode layer is prepared, the sample is cleaned and placed in a magnetron sputtering reaction chamber. A metal Al target with a purity of 99.9995% is used for sputtering. High-purity argon and high-purity nitrogen are used as working gases. The heating rate of the substrate is set to 10°C / min. After substrate pre-sputtering and target pre-sputtering, the substrate temperature is raised to 500°C. The chamber pressure is set to 0.2Pa, the flow ratio of argon and nitrogen is 2.8:1, the sputtering power is set to 120W, and the sputtering time is 10min. A first AlN layer with a thickness of 8nm is prepared. The substrate temperature and target power are kept unchanged, the chamber pressure is still 0.2Pa, the flow ratio of argon and nitrogen is set to 0.2:1, and the sputtering time is 5min. A second AlN layer with a thickness of 4nm is prepared. Finally, a third AlN layer with a thickness of 8nm is prepared by sputtering according to the same parameters as the first AlN layer.

[0077] Step 4: Use tweezers to clamp the grown AlN resistive layer, place one end in a solution of phosphoric acid: acetic acid: nitric acid: water = 16:1:1:2 and etch for 15 seconds. After etching, rinse with deionized water for 120 seconds, and finally blow dry the wafer with N2.

[0078] Step 5: Stick the hard mask template to the grown AlN resistive layer with high temperature tape, place the sample with the hard mask template in the magnetron sputtering reaction chamber, and use a metal Al target with a purity of 99.9995% and a metal Au target with a purity of 99.999%. The equipment is evacuated to 5×10 -7 Pa, first the Al target sputtering power is 450W, the chamber pressure is 0.15Pa, and the sputtering gas Ar is introduced. Under the condition of sputtering temperature at room temperature, a top electrode layer with a thickness of 50nm is deposited. Then the Au target sputtering power is 150W, and a protective layer with a thickness of 50nm is deposited under the same conditions. Finally, the hard mask is removed, and then the device sample is cleaned with acetone, ethanol and deionized water and blown dry with nitrogen to obtain an aluminum nitride-based laminated resistive memory.

[0079] Example 2

[0080] Step 1: Perform thermal oxidation treatment on the P-type Si substrate with the <1 1 1> crystal plane to form a SiO2 layer with a thickness of 100 nm on the upper surface of the Si substrate to obtain a substrate layer. Use acetone, anhydrous ethanol and deionized water to ultrasonically clean the surface of the substrate layer for 3 minutes in sequence and then blow dry with a nitrogen gun.

[0081] Step 2: Using high vacuum evaporation coating equipment, a 10nm Ti metal layer as an adhesion layer and a 100nm Pt metal layer as a bottom electrode layer are deposited on the SiO2 layer of the substrate layer. During the evaporation process, the chamber temperature is about 25°C and the vacuum degree is less than 5×10 -4 Pa, the deposition rate is about

[0082] Step 3: Select high-purity trimethylaluminum as the precursor, high-purity nitrogen-hydrogen mixed gas plasma as the reactant, and high-purity argon as the protective gas and carrier gas; place the sample after the bottom electrode layer is prepared in the reaction chamber, the sample temperature is 300°C, the plasma generation power is 150W; the gas pressure of the reaction chamber is 0.25Torr. Set the flow ratio of argon and nitrogen-hydrogen mixed gas to 3:1, set the number of cycles to 100, and prepare the first AlN layer with a thickness of 10nm. Keep other parameters unchanged, set the flow ratio of argon and nitrogen-hydrogen mixed gas to 1:1, set the number of cycles to 60, and prepare the second AlN layer with a thickness of 6nm. Finally, according to the same parameters as the first AlN layer, cycle 100 times to prepare the third AlN layer with a thickness of 10nm. Each PEALD cycle consists of a precursor injection process, a precursor cleaning process, a reactant injection process, and a reactant cleaning process.

[0083] Step 4: Use tweezers to clamp the grown AlN resistive layer, place one end in a solution of phosphoric acid: acetic acid: nitric acid: water = 16:1:1:2 and etch for 20 seconds. After etching, rinse with deionized water for 120 seconds, and finally blow dry the wafer with N2.

[0084] Step 5: Throw a layer of photoresist on the AlN resistive switching layer after etching. After exposure and development, make the pattern of the top electrode layer, and then use magnetron sputtering to deposit a 100nm thick metal Al layer as the top electrode layer on the surface covered with the patterned photoresist. Then deposit a 100nm thick metal Au on the top electrode layer as a protective layer. Finally, put the grown sample into acetone, use ultrasonic vibration to remove the photoresist and the metal on the photoresist, and obtain an aluminum nitride-based laminated resistive switching memory.

[0085] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. Moreover, the term "include", "comprise" or any other variant is intended to cover non-exclusive inclusion, so that the article or device including a series of elements includes not only those elements, but also other elements that are not explicitly listed. In the absence of more restrictions, the elements defined by the sentence "including one..." do not exclude the existence of other identical elements in the article or device including the elements. "Connect" or "connected" and similar words are not limited to physical or mechanical connections, but can include electrical connections, whether direct or indirect. The orientation or position relationship indicated by "up", "down", "left", "right", etc. is based on the orientation or position relationship shown in the accompanying drawings, which is only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation of the present invention.

[0086] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the protection scope of the present invention.

Claims

1. An aluminum nitride-based stacked resistive random access memory, characterized in that: include: substrate layer, adhesion layer, bottom electrode layer, AlN resistive layer, top electrode layer and protective layer, wherein: The substrate layer, the adhesion layer, the bottom electrode layer and the AlN resistive switching layer are stacked in sequence from bottom to top; The AlN resistive layer comprises a first AlN layer, a second AlN layer and a third AlN layer stacked in sequence from bottom to top, wherein the nitrogen content of the second AlN layer is higher than that of the first AlN layer and the third AlN layer; The top electrode layer is patterned and arranged on the upper surface of the AlN resistive layer, and the protection layer is arranged on the upper surface of the top electrode layer.

2. The aluminum nitride-based stacked resistive random access memory according to claim 1, characterized in that: The substrate layer includes a Si substrate and a SiO2 layer on its upper surface, wherein the Si substrate is a P-type Si substrate with a <1 1 1> crystal plane, and the adhesion layer is located on the upper surface of the SiO2 layer.

3. The aluminum nitride-based stacked resistive random access memory according to claim 1, characterized in that: The adhesion layer is a Ti metal layer with a thickness of 5-10 nm, and the bottom electrode layer is a Pt metal layer with a thickness of 50-100 nm.

4. The aluminum nitride-based stacked resistive random access memory according to claim 1, characterized in that: The nitrogen content of the first AlN layer is 10% to 15%, and the thickness is 8-10 nm.

5. The aluminum nitride-based stacked resistive random access memory according to claim 1, characterized in that: The nitrogen content of the second AlN layer is 40% to 45%, and the thickness is 4-6 nm.

6. The aluminum nitride-based stacked resistive random access memory according to claim 1, characterized in that: The nitrogen content of the third AlN layer is 10% to 15%, and the thickness is 8-10 nm.

7. The aluminum nitride-based stacked resistive random access memory according to claim 1, characterized in that: The top electrode layer is an Al metal layer with a thickness of 50-100 nm, and the protective layer is an Au metal layer with a thickness of 50-100 nm.

8. A method for preparing an aluminum nitride-based stacked resistive random access memory, characterized in that: The aluminum nitride-based stacked resistive random access memory according to any one of claims 1 to 7, wherein the preparation method comprises: Step 1: performing thermal oxidation treatment on the Si substrate to form a SiO2 layer on the upper surface of the Si substrate to obtain a substrate layer; Step 2: depositing a Ti metal layer on the upper surface of the SiO2 layer of the substrate layer to form an adhesion layer, and depositing a Pt metal layer on the upper surface of the Ti metal layer to form a bottom electrode layer; Step 3: stacking a first AlN layer, a second AlN layer and a third AlN layer in sequence from bottom to top on the upper surface of the bottom electrode layer to form an AlN resistive layer, wherein the nitrogen content of the second AlN layer is higher than that of the first AlN layer and the third AlN layer, and the nitrogen content of the first AlN layer, the second AlN layer and the third AlN layer is regulated by the flow ratio of nitrogen gas to argon gas introduced during the preparation process; Step 4: etching the AlN resistive layer to expose a portion of the bottom electrode layer below the AlN resistive layer; Step 5: preparing a patterned top electrode layer on the upper surface of the AlN resistive layer, and preparing a protective layer on the upper surface of the top electrode layer.

9. The method for preparing the aluminum nitride-based stacked resistive random access memory according to claim 8, characterized in that: The step 3 comprises: A first AlN layer, a second AlN layer and a third AlN layer are sequentially deposited on the upper surface of the bottom electrode layer from bottom to top by a magnetron sputtering process to form an AlN resistive layer, wherein when depositing the first AlN layer and the third AlN layer, the flow ratio of argon gas to nitrogen is (2.8-3.2):1, and when depositing the second AlN layer, the flow ratio of argon gas to nitrogen is (0.2-0.6):

1.

10. The method for preparing the aluminum nitride-based stacked resistive random access memory according to claim 8, characterized in that: The step 3 comprises: A plasma enhanced atomic layer deposition process is used to deposit a first AlN layer, a second AlN layer and a third AlN layer in sequence from bottom to top on the upper surface of the bottom electrode layer to form an AlN resistive layer, wherein when depositing the first AlN layer and the third AlN layer, the flow ratio of argon gas to nitrogen-hydrogen mixed gas is (2-3):1, and when depositing the second AlN layer, the flow ratio of argon gas to nitrogen-hydrogen mixed gas is (0.6-1):1.